About Star Architecture. Reflecting on Cities in Europe. - (:unkn) unknown (Springer, 2020)
Cities across the world have been resorting to star architects to brand their projects, spark urban regeneration and market the city image internationally. This book shifts the attention from star architects to star architecture, arguing that the process of deciding about and implementing relevant architectural and urban projects is not the product of any single actor. Star architecture can, in fact, be better studied and understood as assembled by multiple actors and in its relationship with urban transformation. In its 18 chapters, the book presents a multidisciplinary collection of expert contributions in the fields of urban planning, architecture, media studies, urban economics, geography, and sociology, consistently brought together for the first time to deal with this topic. Through a vast array of case studies and analytical techniques touching over 20 cities in Europe, the book shows the positive and more problematic impacts of star architecture with reference to the preservation of built heritage, tourism and media.
Keywords: Stadtimage; Aufwertung; Architektur; Architekt; Großprojekt; Stadtmarketing; Markenzeichen; Repräsentation; Architekturfotografie; Städtetourismus; Massenmedien; Stadtgestaltung; Uferbebauung; Stadtstruktur; Stadtgeographie; Transformation; Weltkulturerbe; Bahnhofsgebäude; Stadtforschung; Urbanismus; Städtevergleich; Fallstudie; Stararchitekt; Beauftragung; Branding; Übertourismus